Cardio-ankle vascular index reflects coronary atherosclerosis in patients with abnormal glucose metabolism: Assessment with 256 slice multi-detector computed tomography - Park, Hyo Eun; Choi, Su-Yeon; Kim, Min Kyung; Oh, Byung-Hee (Journal of cardiology, 2012)
The association between arterial stiffness, as measured by the cardio-ankle vascular index (CAVI), and coronary atherosclerosis, using coronary artery computed tomography (CT), was investigated in the asymptomatic general population, with special interest in subjects with abnormal glucose metabolism. A total of 158 normoglycemic subjects and 373 subjects with abnormal glucose metabolism were evaluated. CAVI was assessed in relation with coronary artery calcium score (CACS) and degree of stenosis detected by CT. The association of CAVI with other clinical parameters was evaluated in patients with abnormal glucose metabolism. CAVI was higher, and CACS and the degree of coronary artery stenosis were both greater compared to the normal group. CAVI showed a significant correlation with CACS and the degree of stenosis (r=0.167, p=0.001; r=0.182, p<0.001, respectively). The cut-off level of CAVI from receiver operating characteristic (ROC) curve was ≥8.0 for predicting ≥50% coronary artery stenosis (area under the curve 0.713, sensitivity 69%, and specificity 61%). CAVI ≥8.0 was independently associated with significant coronary artery stenosis, even after adjusting for age, sex, and presence of hypertension and hypercholesterolemia (odds ratio 3.143, 95% confidence interval 1.004–9.842, p=0.049). CAVI is an independent parameter which reflects coronary atherosclerosis in patients with abnormal glucose metabolism. CAVI can be a useful tool not only to assess arterial stiffness, but also to evaluate the risk for subclinical coronary atherosclerosis in asymptomatic patients.